Uso da acupuntura em crianças com excesso de peso e sintomatologia de ansiedade: um estudo exploratório - Alves, Cínthia Pereira (2012)
This study was justified by the possibility of contributing to the promotion of new ways of treating and preventing childhood anxiety and stress, hypothesized in this study as triggers of cases of overweight. It consists in evaluating the appropriateness of the use of acupuncture on symptomatology indicating anxiety / stress in overweight children. Eleven children took part in this research, six girls and five boys, aged between six and eight years old. Instruments for anthropometric assessment, psychological assessment and energy measuring instruments were used, such as questionnaires, Child Stress Scale and the Ryodoraku method. The intervention consisted of two weekly fifty-minute sessions, for six weeks, adding up to twelve sessions for each child in the sample. During each session, the general health condition of the child was checked, as well as how he had responded to the previous session, and afterwards the evaluation procedures and acupuncture treatment started. With regards to the result obtained in the Child Stress Scale, before and after the acupuncture intervention, it was discovered that three children had moved from stress resistance phase to the alert phase, six children had maintained their scale classification, and two children - who initially had no symptoms indicating stress - began to show symptoms indicative of the alert phase. Regarding the reports obtained from children and their parents, the treatment was able to mitigate the symptoms of anxiety and stress. The results of anthropometric measurements - obtained before and after the intervention showed that five children kept the classification of severe obesity; five children kept the classification of overweight; and one child, initially classified as overweight, happened to be classified as obese. The present study has shed some light on some aspects that come to exist when we face the complexity of operating variables on an epidemic involving inadequate food intake. How does a child get overweight and how does he face it? What factors are considered triggers of stress and anxiety in these children and, what symptoms, manifested by them, may lead to excessive intake of food? How does the child deal with anxiety and what is the role of the family? In what ways can acupuncture help? Answering these questions was one of the challenges of this study and guided the discussion of the data hereby exhibited. This research had as its greatest achievement the dissemination of new evaluation methods and acupuncture treatment, an interface for knowledge of psychological and nutritional nature, that must be considered jointly to face the problem properly. Finally, it is expected that this study has fulfilled its role of working towards the advancement of science and the perspective of improving the quality of life of children who suffer from anxiety / stress and overweight, so there is greater awareness and a greater search for effective actions to enable these children to be healthy and happy, able to live in a plural and harmonious society.